Alimentação do lactente com fissura labiopalatina no primeiro ano de vida - Luiz, Aline Godoi [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Objective: To analyze feeding history and maternal experience with breastfeeding infants with cleft lip and palate. Method: descriptive, cross - sectional, double - approach study: quantitative and qualitative, performed at the outpatient clinic of a reference hospital. Data were collected through structured interviews with 150 mothers; 6 mothers participated in the qualitative study. Univariate and multiple logistic regression analyzes were used, adopting as criterion for inclusion in the multiple model p≤0.20. To consider a factor as associated to the outcome, p was considered critical <0.05, in the multiple analysis. These analyzes were performed in the SPSS program. For the qualitative approach the sample was selected for convenience. The statements of the mothers were transcribed in their entirety and analyzed according to the theoretical framework of content analysis according to the steps proposed by Graneheim and Lundman. After analyzing all the qualitative interviews, a framework was constructed with the themes found from the testimonies, being categorized in themes and sub-themes. Results: Less than half of the mothers knew of the prenatal diagnosis and this factor was associated with exclusive breastfeeding in the first week of life, the physician was responsible for the prenatal guidelines. The prevalent type of fissure was unilateral incisive transforamen and on nutritional status, eutrophy prevailed. The strengths, difficulties and challenges faced by the birth of a child with cleft lip and palate were also verified through latent content analysis. Conclusion: the importance of the guidance of health professionals and the time of discovery of the diagnosis of fissure was evidenced, facilitating thus the coping process and breastfeeding. It demonstrates the need for prior training of all the professionals who will work in the pre- and post-natal period.

Objetivo: Analisar a história alimentar e a experiência materna com a amamentação de lactentes com fissura labiopalatina. Método: estudo descritivo, transversal, de dupla abordagem: quantitativo e qualitativo, realizado no ambulatório de um hospital de referência. Os dados foram coletados por meio de entrevistas estruturadas com 150 mães; 6 mães participaram do estudo qualitativo. Foram realizadas análises de regressão logística univariada e múltipla, adotando-se como critério para inclusão no modelo múltiplo p≤0,20. Para considerar um fator como associado ao desfecho foi considerado p crítico <0,05, na análise múltipla. Essas análises foram realizadas no programa SPSS. Para a abordagem qualitativa a amostra foi selecionada por conveniência. Os depoimentos das mães foram analisados segundo o referencial da análise de conteúdo de acordo com os passos propostos por Graneheim e Lundman. Após a análise das entrevistas qualitativas, os depoimentos foram categorizados em temas e subtemas. Resultados: Menos da metade das mães souberam do diagnóstico da fissura no pré-natal e esse fator associou-se com o aleitamento materno exclusivo na primeira semana de vida, sendo o médico o responsável pelas orientações no pré-natal. O tipo de fissura prevalente foi o transforame incisivo unilateral e sobre o estado nutricional, prevaleceu a eutrofia. Foi constatado também, através das análises do conteúdo latente, as fortalezes, dificuldades e desafios frente ao nascimento de um filho com fissura labiopalatina Conclusão: evidenciou-se a importância da orientação dos profissionais de saúde e da época de descoberta do diagnóstico da fissura, facilitando assim o processo de enfrentamento e o aleitamento materno. Demonstra-se a necessidade da capacitação prévia de todos os profissionais que irão atuar no pré e pós-natal.
Feeding of the infant with cleft lip and palate in the first year of life
Keywords: Fenda labial; Fissura palatina; Análise qualitativa; Análise quantitativa; Aleitamento materno; Métodos de alimentação; Enfermagem; Cleft lip; Palate cleft; Qualitative analysis; Quantitative analysis; Breastfeeding; Feeding methods; Nursing